Asbestos fibers in the gallbladder of patients affected by benign biliary tract diseases. Issue 7 (July 2015) - Grosso, Federica; Randi, Lorenza; Croce, Alessandro; Mirabelli, Dario; Libener, Roberta; Magnani, Corrado; Bellis, Donata; Allegrina, Mario; Bertolotti, Marinella; Degiovanni, Daniela; Rinaudo, Caterina
Abstract : Purpose: This exploratory study aimed to evaluate the presence of asbestos fibers in the biliary tract of patients living in an asbestos-polluted area using scanning electron microscopy. Methods: Thin gallbladder sections were obtained from five patients who were operated on for gallbladder stones and the bile fluid of one of the patients was analyzed using variable-pressure scanning electron microscopy coupled with energy-dispersive spectroscopy. All patients were from Casale Monferrato, Italy, a well-known asbestos-polluted city, where the Eternit factory had operated since the beginning of the century until 1985. Results: All the inorganic phases found in the gallbladder were analyzed for morphology and chemistry. Fibers and particles consistent with minerals defined by law as 'asbestos' were detected in three out of five patients. Conclusion: These findings suggest that asbestos fibers can be found in the gallbladder of patients exposed to asbestos, although how they reach the biliary tract remains unknown. Further studies to confirm these results are under way.